Matizes surrealistas no poema O Amor em visita, de Herberto Helder - Merisio, Priscila Andrea (2019)
In this paper it was researched the relation between the poem O Amor em Visita (1958) by the Portuguese poet Herberto Helder and some elements of surrealism, among them the image, erotic love and new criation of the sacred. There was a brief explanation of the relation of the poet to the technolyric, that is its routes by the experimental and concrete poetry, through experiments with the computer, in the middle of the 60's, and how these shuffles resemble the surrealistic technique of the Exquisite corpse. The hybridism in his structuring of language. General definitions of this movement, which emerged in France in 1930, and the brief history of its reception in Portugal, were also discussed.